1989
DOI: 10.1002/j.1552-4604.1989.tb03362.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Chloroquine and Some of Its Metabolites in Healthy Volunteers: A Single Dose Study

Abstract: Eight healthy volunteers who had not taken chloroquine 2 to 12 months previously participated in a single dose study designed to evaluate the pharmacokinetics of chloroquine and some of its metabolites. Each subject received two tablets of chloroquine sulfate (300 mg base) only. Blood and urine samples were collected just before and periodically after chloroquine administration. These samples were assayed for chloroquine and its N-dealkylated metabolites (monodesethylchloroquine, didesethylchloroquine, 7-chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…Accordingly, the finding that, in humans, DCQ was readily detectable in plasma during the absorption phase of CQ pointed to an enzymatic system with a high capacity (Ducharme and Farinotti, 1996). The predicted nonrenal clearance value of 0.52 Ϯ 0.04 ml/min/kg estimated from the present HLM investigations is in agreement with the one obtained in vivo from normal subjects (0.63-1.02 ml/min/kg; Frisk-Holmberg et al, 1983;Gustafsson et al, 1983;Ette et al, 1989).…”
Section: Chloroquine N-desethylation By Cyp2c8 Cyp3a4 and Cyp2d6supporting
confidence: 87%
See 2 more Smart Citations
“…Accordingly, the finding that, in humans, DCQ was readily detectable in plasma during the absorption phase of CQ pointed to an enzymatic system with a high capacity (Ducharme and Farinotti, 1996). The predicted nonrenal clearance value of 0.52 Ϯ 0.04 ml/min/kg estimated from the present HLM investigations is in agreement with the one obtained in vivo from normal subjects (0.63-1.02 ml/min/kg; Frisk-Holmberg et al, 1983;Gustafsson et al, 1983;Ette et al, 1989).…”
Section: Chloroquine N-desethylation By Cyp2c8 Cyp3a4 and Cyp2d6supporting
confidence: 87%
“…In vivo, the formation rates of DCQ and BDCQ, from CQ and DCQ, respectively, are strongly correlated (r ϭ 0.83) (Ette et al, 1989). In vitro, in HLM, our study demonstrated that DCQ is N-desethylated into BDCQ via an NADPH-dependent system.…”
Section: Chloroquine N-desethylation By Cyp2c8 Cyp3a4 and Cyp2d6supporting
confidence: 52%
See 1 more Smart Citation
“…To enable simultaneous modeling of CQ and DECQ data sets, we fixed the metabolic conversion ratio using published data (11). A limitation of this approach is that BSV contained in CL M /F cannot be assessed, but it becomes a component of a The numbers in parentheses represent the simulated medians for pregnant subjects expressed as percentages of that for the standard dose of 3 tablets (450 mg CQ base) in 3 daily doses for nonpregnant subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The method was partially validated in human plasma. It can be used for estimation of chloroquine in human plasma from clinical studies and measuring residual chloroquine levels in volunteers/patients being enrolled for new antimalarial drug trials, as chloroquine has long half-life of 106.43 ± 10.13 h [35]. …”
Section: Applicationmentioning
confidence: 99%